Subcellular immunochemical localization of acrosin in human spermatozoa during the acrosome reaction and zona pellucida penetration - Tesarík, J; Drahorád, J; Pĕknicová, J (Fertility and sterility, 1988)
The changes in acrosin immunoreactivity in human spermatozoa undergoing spontaneous or chemically induced acrosome reactions were studied by electron microscopic immunocytochemistry with an acrosin-specific monoclonal antibody. Migration of limited amounts of acrosin to the sperm surface was the earliest event characterizing the beginning of the acrosome reaction. The acrosome of such spermatozoa remained morphologically intact, swelled, or showed intraacrosomal vesiculation without any disruption of the plasma and acrosomal membrane integrity. Massive release of acrosin coincided with the fusion of the plasma and outer acrosomal membranes. However, even fully acrosome-reacted spermatozoa always retained some acrosin on the exposed inner acrosomal membrane and in the equatorial segment of the acrosome. This residual acrosin was also detected on spermatozoa within the zona pellucida of human oocytes inseminated in vitro, while the previously released bulk of acrosin remained attached to the surface of the zona pellucida at the site of sperm entry. These findings are compatible with multiple functions of acrosin in human sperm-egg interaction, including sperm-zona pellucida binding, dispersal of acrosomal contents, and facilitation of zona pellucida penetration.
Keywords: zona pellucida; interakce spermie a vajíčka; Immunochemistry; imunochemie; lidé; serinové endopeptidasy; mužské pohlaví; Mice; akrozom; Sperm-Ovum Interactions; Zona Pellucida; akrosin; ženské pohlaví; zvířata; Humans; Acrosome; Acrosin; myši; Serine Endopeptidases; Female; Spermatozoa; spermie; Male; Animals